Development of a low‐dose fast‐dissolving tablet formulation of Newcastle disease vaccine for low‐cost backyard poultry immunisation. (17th May 2014) - Lal, M.; Zhu, C.; McClurkan, C.; Koelle, D. M.; Miller, P.; Afonso, C.; Donadeu, M.; Dungu, B.; Chen, D.
Abstract : The immunisation of backyard poultry is critical for maintaining healthy flocks to provide nutrition and income for low‐resource farmers worldwide. A vaccine presentation for flocks of less than 50 birds could make it more affordable and accessible, increasing uptake and impact. Fast‐dissolving tablets (FDT) of Newcastle disease virus (NDV) vaccine were produced by freeze drying the LaSota NDV strain combined with excipients into tablets containing a small number of doses and packaged in polymer blister sheets. The NDV‐FDT vaccine maintained virus stability for more than six months at 4°C, based on plaque assay and egg infectivity dose data. Stability was further confirmed in a challenge study, where the tablet vaccine elicited a strong immune response and provided 100 per cent protection to vaccinated chickens infected with a virulent strain of NDV. The vaccine tablet can be diluted in water (no needle or syringe required) and administered either in drinking water or with a dropper via an intraocular and/or intransal route. Results indicate that FDTs containing a small number of doses are a feasible presentation for backyard poultry farmers. The compact packaging of the FDTs will also provide cost savings in storing and distributing the vaccine in the cold chain.